PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH PADA TABUNGAN BTN BATARA (KASUS : PT. BANK TABUNGAN NEGARA (PERSERO) TBK., CABANG MEDAN) - Alexander Aloysius; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The quality of service is the level of excellence that is expected and control over that advantage to meet the wishes of costumers. As a result of service quality would give customers or costumers in banking to be faithful use the services of the banking.This study aims to know the influence of the quality of services to the loyalty of costumers in the BTN Batara (PT. Bank Tabungan Negara (Persero) Tbk of Medan) as well as to test the influence of both these variables. The author using the method of analysis descriptive and some theory of the quality of service and loyalty of customers. The indicators used in a variable is an independent is realibility, responsiveness, assurance, empathy, and physical evidence and variable strapped to is the loyalty of customers. Gathering data using the questionnaire and interview. The sample used is accidental sampling. The source data used is the primary or data obtained directly from the questionnaire and interview. Data secondary is the data obtained from the customer service and the public company the bank, Bank Tabungan Negara of Medan.The results of this is the tests are conducted can be concluded that variable the quality of service used to explain 73,7% impact on the variables the loyalty of customers while the rest of his 27,3% affected or be explained by other variables that are not included in this research.Key word : The quality of service, The loyalty of customers